Vitis Vinifera Leaf Extract Protects Against Glutamate-Induced Oxidative Toxicity in HT22 Hippocampal Neuronal Cells and Increases Stress Resistance Properties in Caenorhabditis Elegans - Duangjan, Chatrawee; Rangsinth, Panthakarn; Zhang, Shaoxiong; Gu, Xiaojie; Wink, Michael; Tencomnao, Tewin (Frontiers in Nutrition, 2021)
Vitis vinifea has been used for traditional medicines, food, beverages, and dietary antioxidant supplements. The chemical compositions and biological activities of the fruits and seeds have been extensively investigated. However, the biological effects of the leaves are limited and its anti-neurodegeneration or anti-aging activities are little known. The current work aims to study the beneficial effects of V. vinifera leaf extract on neuroprotective effects in HT22 cells, anti-aging and oxidative stress resistance properties in the Caenorhabditis elegans model. The phytochemical composition of the ethanol extract was analyzed using LC-MS and RP-HPLC. The beneficial effects of V. vinifera ethanol extract (VVE) on antioxidant properties, neuroprotective effects and the underlying mechanisms were studied by in vitro and in vivo study. In HT22 cells, we found that VVE has a protective effect against glutamate-mediated oxidative stress-induced cell death. The gene expression of cellular antioxidant enzymes such as SODs, CAT, GPx and, GSTs were up-regulated by VVE treatment. Moreover, VVE was also shown to alleviate oxidative stress and attenuate ROS accumulation in C. elegans. We demonstrated that VVE can up-regulate the expression of stress-response genes sod-3 and gst-4 as well as down-regulate the expression of hsp-16. Our results suggest that the oxidative stress resistance properties of VVE are possibly involved in DAF-16/FoxO transcription factors. VVE reduced age-related markers (lipofuscin) while did not extend the life span of C. elegans under normal conditions. This study reports the neuroprotective effect and antioxidant activity of V. vinifera leaf extract and suggests its potential as a dietary supplement and alternative medicine to defend against oxidative stress and age-related diseases.